Bereavement overload and its effects on, and related coping mechanisms of health care providers and ward administrators at National District Hospital in Bloemfontein, Free State - Zaid Allie; Edith Le Roux; Khantse Mahlatsi; Boitumelo Mofokeng; Zara-Anne Ramoo; Khanyisile Sibiya; Gina Joubert; Jan P Van Rooyen; Hanneke Brits (AOSIS, 2018)
Background: Patient death is an event that all health care workers will face at some point. Beyond the family, the greatest emotional strain is on people who work directly with the patient and family. Bereavement overload occurs after multiple losses without time for normal grief in between. Aim: To investigate bereavement overload, its effects and related coping mechanisms of personnel working in adult medical wards. Setting: Four adult medical wards at National District Hospital, Bloemfontein. Methods: An analytical cross-sectional study design was performed with the aid of an intervieweradministered questionnaire. The target population included health care providers (13 doctors and 20 nurses), eight final-year medical students, and four administrative staff working in thefour adult medical wards at National District Hospital, during August to October 2016. Results: Half (48.9%) of the 45 participants reported bereavement overload. None of the medical students reported bereavement overload compared to 60.0% of nurses, 75.0% of administrative staff and 53.9% of doctors. Nearly two-thirds (64.5%, n = 29) stated that they suffered from compassion fatigue. The majority of participants (62.2%) used only positive coping mechanisms. The use of negative coping mechanisms correlated directly with a longer duration in the medical field. Conclusion: With a 49% prevalence of bereavement overload, it is important that support systems are in place to prevent the effects of negative coping mechanisms. The desirable outcome is that health care providers, who suffer from bereavement overload, experience compassion satisfaction and become more dedicated to the patients' well-being without expense to themselves.